Gold nanoparticles for improved electron microscopic detection of Potato virus M in potato leaves and tubers - Raigond, Baswaraj; A, Jeevalatha; Kumar, Ravinder; Kochhar, Tarvinder; Kaundal, Priyanka; Roach, Shivani; Kumar, Rajender; Singh, B P (Potato Journal, 2016)
The present study was aimed to develop immuno-gold electron microscopic technique to detect Potato virus M (PVM) in potato leaves and tubers. In-house raised antibodies against PVM were used for immuno globulin G (IgG) purification and conjugated with colloidal gold (CG) nanoparticles. The electron microscope (EM) studies revealed the presence of good concentrations of elongated particles coupled with several IgG conjugated gold (IgG-CG) nanoparticles either single or in small clusters indicating the presence of PVM. The cross reactivity and sensitivity of developed technique was examined with the pure cultures of PVY, PVS, PVA, PVX and PVM. Wherein, it revealed that only homologous virus (PVM) was decorated but not the others. The technique was validated with suspected potato leaf samples collected from field. The results of the optimized technique were parallel confirmed by RT-PCR wherein, the results supplemented the developed technique. The technique was further extended to detect PVM in potato tubers where elongated virus particles coupled with gold nanoparticles were observed revealing the presence of Potato virus M in potato tubers. This study describes a useful method that allows us for same day diagnosis and contributes significantly towards a rapid and clear identification of PVM in potato leaves and tubers.